Relationship Between Nutritional Status Based On Bmi/Age To The Total Number Of Oral Bacteria In Children Aged 5-12 Years (Analytical Study At Sdn Bandarharjo 02 North Semarang) - Salma Umi Rafiah; Welly Anggarani; Rochman Mujayanto (Jurnal Medali, 2026)
Background: Unbalanced nutritional intake can affect the occurrence of disorders in the oral cavity, such as disorders of the function and structure of the soft tissues of the mouth, especially at the corners of the lips and tongue so that microbial growth increases due to the decomposition of food. BMI/U is a nutritional status assessment index that is often used to detect nutritional problems in children. Accumulation of bacteria in the oral cavity causes poor oral hygiene and causes the development of microbes that can lead to inflammation. Aim: This study aims to determine the relationship between nutritional status based on BMI/AGE and the total number of bacteria in the oral cavity of children aged 5-12 years. Mthode: The research method used is observational analytical research with laboratory experiments. The research subjects required were 100 children, aged 5-12 years. The sampling technique used purposive sampling. Results: From the results of the data analysis, a significance value of 0.028 was obtained (p <0.05). Conclusion: The conclusion of this study is that there is a unidirectional correlation between nutritional status and the number of bacteria in the oral cavity of children.